Determination of the Genetic and Synergistic Suppression of a Methoxyfenozide-Resistant Strain of the House Fly Musca domestica L. (Diptera: Muscidae) - Shah, R M; Abbas, N; Shad, S A; Binyamin, M (Neotropical entomology, 2018)
Musca domestica Linnaeus (house fly, Diptera: Muscidae) is a major veterinary and medical important pest all over the world. These flies have ability to develop resistance to insecticides. The present trial was performed to discover the inheritance mode (autosomal, dominance, number of genes involved) and preliminary mechanism of methoxyfenozide resistance in order to provide basic information necessary to develop resistance management strategy for this pest. A strain of M. domestica (MXY-SEL) was exposed to methoxyfenozide for 44 generations which developed a 5253.90-fold level of resistance to methoxyfenozide. The overlapping fiducial limits of LC50 values of the reciprocal crosses, F1 (MXY-SEL ♂ × Susceptible ♀) and F1† (MXY-SEL ♀ × Susceptible ♂), suggest that inheritance of methoxyfenozide resistance was an autosomal and likely completely dominant trait (DLC = 0.93 and 0.94 for F1 and F1†, respectively). Backcrosses of the F1 with the parental MXY-SEL or Susceptible population predict a polygenic mode of inheritance. Piperonyl butoxide significantly altered the LC50 values, suggesting enhanced detoxification by cytochrome P450-dependent monooxygenases is a major mechanism of resistance to methoxyfenozide in the MXY-SEL strain. The estimated realized heritability was 0.07 for methoxyfenozide. These results would be helpful for the better management of M. domestica.
Keywords: zvířata; Houseflies; Insecticides; Enzyme Inhibitors; Insecticide Resistance; Selection, Genetic; Multifactorial Inheritance; rezistence k insekticidům; systém (enzymů) cytochromů P-450; Cytochrome P-450 Enzyme System; Animals; juvenilní hormony; selekce (genetika); křížení genetické; inhibitory enzymů; Hydrazines; hmyzí geny; hydraziny; moucha domácí; Crosses, Genetic; multifaktoriální dědičnost; insekticidy; Genes, Insect; Juvenile Hormones